IMPROVING THE SYSTEM OF REMUNERATION OF PERSONNEL OF THE ENTERPRISE ON THE BASIS OF KPI - S. M. Klimkovich; E. V. Korneevets (Литьë и металлургия)
The advantages of the system of awarding of staff on key performance indicators are considered. The structure of formation of motivation on the basis of KPI. The main tasks when building a bonus system on the basis of KPI. Justification the use of key performance indicators in the enterprise is made. The scheme of construction of system of motivation of personnel KPI is proposed.